Calculation of Ionospheric Disturbances of Earthquakes in Europe with TEC Anomalies - Okten, M. Baran; Can, Zehra; Aydin, O. Faruk; Dokur, Almina; Aydin, Anjelika (IEEE, 2022)
The Earth's ionosphere, which is a natural plasma, can be affected by many factors such as spacecraft launches, explosions in mines, energy fluctuations created by nuclear tests that will cause energy release, solar geomagnetic storms, and seismic activities. Total Electron Content (TEC) is among the most practical ways to study these disturbations. Significant changes occur in the TEC value, especially before and after large earthquakes. For this reason, it is of great importance to examine the anomalies created by earthquakes to establish the lithosphere-ionosphere connection more clearly. In this study, the TEC anomalies 15 days before and 15 days after the earthquakes of 6 and above in the European continent between 2010 and 2020 were calculated using the data obtained from the GIRO ionosondes located in an imaginary circle formed by the earthquake strain radius and analyzed in the heat map collectively. In this way, the ionospheric anomalies caused by all the examined earthquakes could be analyzed clearly on a daily and hourly basis. In particular, it has been determined that negative anomalies start in the evening hours of twelve days before the earthquakes and last until the morning, and positive anomalies increase two days before the earthquake. Anomalies were identified eight days before the earthquake and were large and prolonged. It was determined that positive anomalies appeared four days after the earthquake.
Keywords: Engineering; Remote Sensing; Optics; Telecommunications